Insulin-Like Growth Factor-I Concentration in the Follicular Fluid of Bali Cattle and Its Role in the Oocyte Nuclear Maturation and Fertilization Rate - H. Hasbi; S. Gustina; N.W. K. Karja; I. Supriatna; M. A. Setiadi (Faculty of Animal Science, Bogor Agricultural University, 2017)
The objective of this study was to determine the concentration of IGF-I in the follicular fluid (FF) of Bali cattle and its role in the nuclear maturation and fertilization rate. The follicular fluid was collected by the aspiration technique, then it was centrifuged at 1500 g for 30 min at 24oC. The supernatant was collected and stored at -20oC until being used in the experiment for analysis of IGF-1. A total of 1105 oocytes were used in this study. The oocytes were matured in M199 without supplementation of bovine serum albumin, with supplementation of BSA, and with supplementations of 10% FF (v/v) from the follicle with diameter Ø<4 mm, 4≤Ø<6 mm, 6≤Ø<8 mm, and Ø≥8 mm at the luteal phase and then fertilized. The results showed that the concentrations of IGF-I in the FF obtained during the luteal phase was significantly higher (P<0.05) compared to those obtained during follicular phase. The IGF-I concentrations in the follicular fluid of follicle with diameter smaller than 6 mm were significantly higher (P<0.05) compared to those with diameters larger than 6 mm. The percentage of nuclear maturation rate of oocytes cultured with FF obtained from follicle with diameter <4 mm was significantly higher (P<0.05) compared to those obtained from the other groups of follicle diameters. The supplementation of maturation media with BSA and FF were able to improve fertilization rate significantly (P<0.05) compared to maturation media without BSA. In conclusion, the concentration of IGF-I in the follicular fluid obtained during the luteal phase was higher compared to those obtained during the follicular phase. The IGF-I concentrations in the follicular fluid of smaller follicles (diameter <6 mm) were higher compared to those in the large follicles (diameter ≥6 mm). The supplementation of FF can improve the nuclear maturation and fertilization rate